Exploring Tax Aggressiveness Using DTAX: Evidence From Basic Material Companies - Keevin Verdianto; Michael (Ilomata International Journal of Tax and Accounting, 2026)
Indonesia continues to face challenges in optimizing tax revenue, as indicated by a low tax ratio of 12.1%, which is far below both the OECD and Asia-Pacific averages. This condition may be associated with low tax compliance and aggressive tax planning by corporations, particularly multinational firms. Nevertheless, prior studies primarily employ conventional tax aggressiveness proxies such as effective tax rate which may obscure discretionary tax behavior at the sectoral level. This study investigates tax aggressiveness in basic material companies listed on the Indonesia Stock Exchange, by examining the role of transfer pricing, thin capitalization, capital intensity, and sales growth during the 2019–2024 period. By employing Discretionary Permanent Differences (DTAX) as a proxy for tax aggressiveness, this study captures discretionary components of permanent book tax differences that are closely linked to tax-planning choices, making it theoretically consistent with agency theory. The study conducts 168 firm-year observations from 28 companies and applies panel data regression under Common Effect Model with Estimated Generalized Least Squares (EGLS). The results indicate that thin capitalization exerts a negative and statistically significant linkage on tax aggressiveness, indicating that despite the potential tax benefit of interest deductions, regulatory oversight reduces the likelihood of using debt as an aggressive tax strategy. In contrast, transfer pricing and sales growth exhibit positive coefficients, while capital intensity shows a negative coefficient, but are statistically insignificant when tested individually. This study presents an evaluation of the effectiveness of government tax policies in encouraging more cautious and compliant corporate tax planning.